Introduction to the phylogenetic analysis of Maxillaria Ruiz & Pav. (Maxillariinae, Orchidaceae) - Sitko, Magdalena; Tukałło, Piotr; Górniak, Marcin (Biodiversity: Research and Conservation, 2006)
Maxillaria Ruiz & Pav. is the largest genus of the subtribe Maxillariinae Lindl. (Orchidaceae) and also one of largest genera within the subfamily Vandoideae Endl. Maxillaria contains mainly tropical and subtropical orchids. It is a highly disorderly genus because of the great number of species as well as a multitude of features occurring in many combinations. Both the number of species assigned to this genus, and the infrageneric classifications of Maxillaria, are not clearly resolved yet. In this paper, a phylogenetic study based on Internal Transcribed Spacer (ITS) sequences is presented. The results show the monophyletic character of the subtribe Maxillariinae and the paraphyletic character of Maxillaria.